Whose forest is this, anyway?: criteria and indicators on access to resources - Colfer, C.J.P.; Salim, A.; Tiane, A.M.; Tchikangwa, B.; Sardjono, M.A.; Prabhu, Ravi (CAB International, 2001)
This chapter provides a brief history of the social component of Center for International Forestry Research (CIFOR)'s project, 'Assessing sustainable forest management: testing criteria and indicators', with special reference to the issue of security of inter-generational access to resources (SIAR). It first presents an overview of the literature on assessing SIAR; then the social criteria and indicators (C&I) "Best Bets" and some method for assessing them. It concludes with earliest tentative findings relating to the possible causal links between sustainable forest management on the one hand, and one element in SIAR (sharing of forest benefits), on the other. In this analysis, It used data from two forest-rich sites (Bulungan, East Kalimantan, Indonesia and the Dja Reserve, Cameroon) and two forest-poor sites (Long Segar, East Kalimantan and Mbalmayo, Cameroon). It was found that timber companies and the government were perceived to have dominant shares of cash and timber in all sites, though to varying degrees; and that local communities were seen to have dominant shares of other forest products. Differences based on forest quality were not striking. It concludes by discussing on plans and recommendations for future research.